A Prognostic Energy Optimization Technique with unified power quality conditioner for energy stabilization in grid system. (September 2021) - Kavithaa, G.; Balakrishnan, P.; Yuvaraj, S.A.
Abstract: Since the past decade, the power quality system has evolved dynamically due to smart grid technology. In this unique circumstance, energy management and optimal scheduling of different resources are becoming significant and challenging in the Large Scale Distribution Network (LSDN). Due to variable loads connected to the bus system in an uncertain LSDN, the Unified Power Quality Conditioner (UPQC) based compensator is implemented to resolve this difficulty and to compensate the power flow in the bus system. In this work, Prognostic Energy Optimization Technique (PEOT) with UPQC-based self-organizing network is introduced to improve the Optimal Power Flow (OPF); it will also reduce the power loss and enhance power flow in the grid power system. All the bus power flow data are shared in the Internet of Things (IOT) for users to identify the faulty bus location. The performance of the UPQC based 14-bus system is evaluated in MATLAB 2017b software environment.